2022
DOI: 10.3390/molecules27103151
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Dioscin against Parkinson’s Disease via Adjusting Dual-Specificity Phosphatase 6 (DUSP6)-Mediated Oxidative Stress

Abstract: Exploration of lead compounds against Parkinson’s disease (PD), a neurodegenerative disease, is of great important. Dioscin, a bioactive natural product, shows various pharmacological effects. However, the activities and mechanisms of dioscin against PD have not been well investigated. In this study, the tests on 6-hydroxydopamine (6-OHDA)-induced PC12 cells and rats were carried out. The results showed that dioscin dramatically improved cell viability, decreased reactive oxygen species (ROS) levels, improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…yunnanensis are primarily steroidal saponins that have anti-inflammatory and anti-tumor effects [ 26 , 27 , 28 , 29 , 30 , 31 ]. The 2020 edition of the Chinese Pharmacopoeia includes polyphyllin I, II, and VII as quality control indicators [ 2 ], and studies have also shown that polyphyllin H has hemostatic effects [ 32 ], dioscin has strong immunomodulatory effects [ 33 , 34 , 35 ], and pseudoprotodioscin can reduce the gene expression regarding the synthesis of cholesterol and triglycerides [ 36 ]. In addition, Gao et al [ 37 ] showed that the saponins of polyphyllin can scavenge reactive oxygen species and significantly inhibit lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…yunnanensis are primarily steroidal saponins that have anti-inflammatory and anti-tumor effects [ 26 , 27 , 28 , 29 , 30 , 31 ]. The 2020 edition of the Chinese Pharmacopoeia includes polyphyllin I, II, and VII as quality control indicators [ 2 ], and studies have also shown that polyphyllin H has hemostatic effects [ 32 ], dioscin has strong immunomodulatory effects [ 33 , 34 , 35 ], and pseudoprotodioscin can reduce the gene expression regarding the synthesis of cholesterol and triglycerides [ 36 ]. In addition, Gao et al [ 37 ] showed that the saponins of polyphyllin can scavenge reactive oxygen species and significantly inhibit lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…DUSPs can participate in various cellular functions by regulating the MAPK pathway, thereby playing a role in the regulation of different diseases [22,23]. DUSP6 (dual-specificity phosphatase 6) is a member of the DUSP family that specifically targets the extracellular signal-regulated kinases (ERK) pathway, and it has a very high substrate specificity and dephosphorylation of the ERK pathway [24]. According to the literature, DUSP6 was confirmed to be negatively correlated with the level of Kirsten rat sarcoma viral oncogene homolog expression in experiments related to human non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%